Numerical = periodic homogenization. Issue 1 (17th December 2018) - Peterseim, Daniel; Varga, Dora
Abstract: In our work, we try to bridge the existing theory of classical homogenization and the practical methods in numerical homogenization. We suggest an effective coefficient, which stems from the LOD method and which is based on a triangulation of the underlying domain. It turns out that in the case the diffusion coefficient has periodic structure and for a suitable choice of the mesh, the suggested coefficient coincides with the homogenized coefficient from classical homogenization.